Fused Deposition Modelling Approach in Recycled Polypropylene/Aluminum Powder Composites for Sustainable Development - Rana, Manveer; Kumar, Mohit; Kumar, Ranvijay (Applied Science and Engineering Progress, 2024)
Polypropylene (PP) is a versatile and widely used thermoplastic polymer that has found its way into various aspects from packaging materials and consumer products to automotive components and industrial applications. However, this widespread use of polypropylene also presents a significant challenge in the disposal of polypropylene waste and its durability aspects. So, the fused deposition modeling (FDM) technique arises as compiling outcomes for recycling discarded PP waste to create functional products. The properties of FDM components produced from recycled polypropylene (r-PP) are notably inferior to those of virgin PP FDM counterparts. Hence, it becomes imperative to comprehend the substantial alterations that r-PP undergoes during successive extrusion processes, including chain scission, alterations in viscosity, and reductions in breaking strength. The incorporation of additives has emerged as a promising solution to enhance the performance of r-PP. In this context, the present study explores the development of a novel composite material by blending r-PP with aluminum powder. The combination of these materials leverages the sustainability benefits of r-PP and the excellent thermal and mechanical properties of aluminum, making it a promising candidate for a wide range of applications. The tensile results show a significant increase in Young’s modulus for pre-heat treated composite specimen at 214 ℃ extrusion temperature. The SEM fractrographic analysis confirms the homogenized distribution after pre-heat treatments. XRD results analyzed the degree of crystallinity in the composite specimens.